A Comparative Study on the Efficacy of Lignocaine with Adrenaline and Ropivacaine for Post Tonsillectomy Pain Relief - Joseph, Anupriya; Ashok, Vivekanand; Parammal Ayyappankandi , Nazneen; Krishna , Swathi; Sunil , Gouri (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2025)
Background: Post-operative pharyngeal pain is one of the major problems with tonsillectomy. Thus, Adequate analgesia is crucial in the immediate post-operative period, which enables the patients to speak and swallow normally. Though there are various routes to administer the anesthetic agents, intraoperative peritonsillar injection of local anesthetics is one of the preferred technique. Aim: The present study was done to find out the effectiveness of lignocaine with adrenaline versus ropivacaine in controlling post-operative pain and intra operative blood loss. Methods: The study was conducted at Karuna Medical College, Kerala India, in which patients undergoing tonsillectomy for standard indications were included in the study. The patients were randomly divided into two groups- Group L and group R. The anesthetic agent was then injected into the peritonsillar region. Group L received lignocaine and group R received Ropivacaine. Intraoperative blood loss and pain during swallowing, speech, and at rest were assessed using visual analogue scale at 4, 8, 12 and 24-hours post-surgery. Results: Lignocaine group showed slightly higher pain levels during swallowing, speaking, and at rest compared to ropivacaine at various intervals. Mean pain scores were significantly lower in Group R, at 4, 8, 12, and 24-hours post-surgery, with p-values <0.05. Additionally, ropivacaine demonstrated superior pain control, particularly during speech and swallowing. No significant correlations were observed between age, gender, or indications and pain levels. Conclusion: Both ropivacaine and lignocaine with adrenaline can be used as effective local anesthetics in achieving post-operative pain control after tonsillectomy. Ropivacaine provides significantly better postoperative pain control compared to lignocaine with adrenaline in patients undergoing tonsillectomy.